Engaging student interpreters in vocabulary building: Web search with computer workbench. Issue 3 (3rd March 2014) - Lim, Lily
Abstract This paper investigates the usefulness of Web portals in a workbench for assisting student interpreters in the search for and collection of vocabulary. The experiment involved a class of fifteen English as a Foreign Language (EFL) student interpreters, who were required to equip themselves with the appropriate English vocabulary to handle an interpreting task they had been assigned. The subjects were given the same topic for vocabulary building in two stages – one stage without and the other stage with the use of the workbench. They were not allowed to repeat vocabulary items in the two stages. They documented their experience in vocabulary preparation in the first stage, and provided think-aloud protocols for the second stage. They also completed a questionnaire and submitted two portfolios. The vocabulary portfolios compiled during the two stages were then compared. The results indicate that, with the use of the workbench, the subjects were more efficient in performing the task of building vocabulary by searching for the required vocabulary, and were able to build a vocabulary portfolio that was larger in size and richer in variety. The data also reveal that most students make use of Web portals that have a specific focus, rather than general search engines. The findings provide important information to support the use of the workbench as a tool for training EFL student interpreters in vocabulary building, and also show that guided Web portals are essential for users who need to perform Web-based language learning activities to achieve efficient search results.